2006
DOI: 10.1681/asn.2005060659
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Sodium Intake Regulates the Ubiquitin-Protein Ligase Nedd4-2 in the Renal Collecting System

Abstract: The activity of the epithelial sodium (Na ؉ ) channel (ENaC) in the aldosterone-sensitive distal nephron (ASDN) needs to be tightly regulated to match urinary Na ؉ excretion with dietary Na ؉ intake. The ubiquitin-protein ligase Nedd4-2, which in vitro interacts with ENaC subunits and reduces ENaC cell surface abundance and activity by ubiquitylation of the channel, may participate in the control of ENaC. This study confirms in vivo by reverse-transcriptase-PCR that Nedd4-2 is expressed throughout the nephron … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
47
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
4
1

Relationship

3
7

Authors

Journals

citations
Cited by 62 publications
(49 citation statements)
references
References 51 publications
2
47
0
Order By: Relevance
“…Immunofluorescence analysis showed that Cre recombinase is expressed in every tubular cell along the renal tubules of doxycycline-treated KO, but not in the blood vessels ( Figure 1A). Consistent with previous report (26), Nedd4L mRNA could be detected in the proximal tubule (PT), DCT, CNT, and CD in microdissected tubules of control mice, but not in KO ( Figure 1B). Western blot on total kidney lysates revealed a decrease of the 130-kDa NEDD4-2 protein in doxycycline-treated KO mice ( Figure 1C).…”
Section: Resultssupporting
confidence: 92%
“…Immunofluorescence analysis showed that Cre recombinase is expressed in every tubular cell along the renal tubules of doxycycline-treated KO, but not in the blood vessels ( Figure 1A). Consistent with previous report (26), Nedd4L mRNA could be detected in the proximal tubule (PT), DCT, CNT, and CD in microdissected tubules of control mice, but not in KO ( Figure 1B). Western blot on total kidney lysates revealed a decrease of the 130-kDa NEDD4-2 protein in doxycycline-treated KO mice ( Figure 1C).…”
Section: Resultssupporting
confidence: 92%
“…study 22 indicate that chronic activation of MR leads to decreased collecting duct expression of Nedd4-2. A key finding of our study is that the kidney is able to circumvent a genetic obligation for avid sodium reabsorption.…”
Section: ␤Hsd2mentioning
confidence: 80%
“…This steroid hormone produces salt-sensitive hypertension partly by stimulating renal Na ϩ and Cl Ϫ transporters such as ENaC and pendrin (12,22,24,36). Aldosterone increases ENaC surface expression largely through a mechanism that involves the ubiquitin ligase NEDD4-2 (20,33). After binding to NEDD4-2, transporters such as ENaC are ubiquitinated and then endocytosed and degraded (10,20,27).…”
Section: Discussionmentioning
confidence: 99%